ASPECTS OF GOVERNANCE OF SOCIOECONOMIC PROCESSES UNDER POLICIES OF RESTRICTIONS - Berezhnoy, Vladimir; Martseva, Tatiana; Berezhnaya, Elena; Glaz, Julia; Tolmachev, Alexey (Revista Inclusiones, 2020)
The paper analyses the aspects of socioeconomic processes during a pandemic (as exemplified by the coronavirus) and government policies balancing the interests of the state vs. the mechanism of guarantees of human rights and freedoms. The aim of this study is to analyse the instruments of national and international law and government tactics and to determine the effects of policies of restrictions on socioeconomic processes. Studies of regulations of international law and political cases of different countries have led the authors to the conclusion of the inefficiency of the legal and political regulatory mechanism governing socioeconomic processes, which means the foundations of international regulations in addressing socioeconomic processes should be revisited to reflect novel threats and risks. This underscores the novelty and relevance of the present research. A central highlight is that political powers in a country should exert every effort to ensure the measures to contain the spread of infection are strictly compliant with the standards of international human rights law and are not used to manipulate social, political and economic processes. The aspects of administering socioeconomic processes when policies of restrictions are in place are primarily determined by the importance of guaranteeing rights, on the one hand, and maintaining national security, on the other hand. Government social policies refer to two levels of standards, universal international norms and internal laws setting the legal space-time for implementing conventions, treaties and accords. If threats arise that impact the level of protection of citizens (and in some cases non-citizens), the state has the power to introduce temporary restrictions and limitations of rights and freedoms. The global community has come across an objective threat to human life and health, which required the introduction of tough and politically and economically controversial measures